Soil microbes alter plant fitness under competition and drought. (27th February 2019) - Fitzpatrick, Connor R.; Mustafa, Zainab; Viliunas, Joani
Abstract: Plants exist across varying biotic and abiotic environments, including variation in the composition of soil microbial communities. The ecological effects of soil microbes on plant communities are well known, whereas less is known about their importance for plant evolutionary processes. In particular, the net effects of soil microbes on plant fitness may vary across environmental contexts and among plant genotypes, setting the stage for microbially mediated plant evolution. Here, we assess the effects of soil microbes on plant fitness and natural selection on flowering time in different environments. We performed two experiments in which we grew Arabidopsis thaliana genotypes replicated in either live or sterilized soil microbial treatments, and across varying levels of either competition (isolation, intraspecific competition or interspecific competition) or watering (well‐watered or drought). We found large effects of competition and watering on plant fitness as well as the expression and natural selection of flowering time. Soil microbes increased average plant fitness under interspecific competition and drought and shaped the response of individual plant genotypes to drought. Finally, plant tolerance to either competition or drought was uncorrelated between soil microbial treatments suggesting that the plant traits favoured under environmental stress may depend on the presence of soil microbes. In summary, our experiments demonstrate that soil microbes can have large effects on plant fitness, which depend on both the environment and individual plant genotype. Future work in natural systems is needed for a complete understanding of the evolutionary importance of interactions between plants and soil microorganisms.